Household Finances, Well-Being and Subjective Financial Situation: An Empirical Analysis of Household Survey Data - Gray, Daniel (My University, 2014)
This thesis aims to contribute to the existing literature relating to household finances and well-being by considering three related, yet distinct, topics. Recently, household finances and well-being have received increasing academic attention for numerous reasons, including the recent economic downturn. This thesis aims to explore household finances, well-being and the relationship between them. Chapter 2, the first empirical chapter, investigates the determinants of household financial portfolio allocation in the U.S. by exploring the proportion of total financial assets allocated to four distinct asset categories. The chapter employs a variety of econometric techniques to ascertain whether accounting for the proportional nature of the dependent variables influences the estimated coefficients. The analysis shows that it is important to separate decisions over holding different asset types and the proportions held. Chapter 3 explores the relationship between the household’s financial position and well-being in Britain, Australia and Germany. Building on the existing literature by employing panel data techniques, the analysis suggests that subjective financial position is an important determinant of well-being, while monetary levels of the household’s financial situation have a limited direct impact on well-being. Chapter 4 aims to ascertain the determinants of the subjective financial position and further explores the relationship between the head of household’s subjective financial position and overall life satisfaction in Australia and Germany. It is found that assets and net wealth are positively related to the subjective financial position, whereas debt levels are inversely related. In addition, risk attitudes are found to be an important determinant of subjective financial position. For Australia, once a joint modelling approach is implemented, there is no statistical relationship found between the head of household’s subjective financial position and overall life satisfaction. In Germany, the subjective financial position appears to mediate the relationship between monetary financial measures and overall life satisfaction.
Keywords: Income & Finance; Health -- Wellbeing; Families -- Households; Families and relationships; Health and wellbeing; Income, wealth and finances; Income & Finance; Families; Health; Wellbeing; Households; Health and wellbeing; Income, wealth and finances; Families and relationships